Charpy impact testing to assess the quality and durability of unidirectional CFRP rods. (May 2016) - Tanks, Jonathon; Sharp, Stephen; Harris, Devin
Abstract: The most common mechanical test methods for assessing quality and durability of unidirectional fiber reinforced polymer (FRP) composites include uniaxial tension and short-beam shear (SBS) tests, which measure residual fiber-dominant and matrix-/interface-dominant strengths, respectively. Although commonly used to qualitatively evaluate fracture toughness in metals through energy absorbance, the Charpy impact test can also be used for FRP to qualitatively compare different materials or treatments. This study examines the Charpy impact test for assessing the manufacturing quality and environmental durability of unidirectional carbon FRP (CFRP) rods. The purpose is to evaluate this test for the rapid assessment of CFRP materials, compared to the more commonly used SBS test. Fractographic analysis supports the mechanical test results when correlating between test methods. Ultimately, results from the comparative impact testing demonstrated that the method induces similar failure modes as the SBS test, providing information to qualitatively compare between commercial products or conditioning effects.